2023
DOI: 10.4103/ijo.ijo_2981_22
|View full text |Cite
|
Sign up to set email alerts
|

Tear biomarkers in dry eye disease: Progress in the last decade

Abstract: Dry eye disease (DED) is a commonly occurring, multifactorial disease characterized by reduced tear film stability and hyperosmolarity at the ocular surface, leading to discomfort and visual compromise. DED is driven by chronic inflammation and its pathogenesis involves multiple ocular surface structures such as the cornea, conjunctiva, lacrimal glands, and meibomian glands. The tear film secretion and its composition are regulated by the ocular surface in orchestration with the environment and bodily cues. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 110 publications
0
12
0
3
Order By: Relevance
“…As surrogate markers of disease severity, there are elevated concentrations of IL-1β, IL-2, IL-4, IL-6, IL-9, IL-12, IL-17A, IFN-γ, and TNF-α cytokines, and CCL2, CCL3, CCL4, and CXCL8 chemokines. The levels of MMP-9, FGF, VEGF-A, IL1RA, sICAM-1, and sTNFR1 soluble receptors, NGF, substance P, and serotonin neurotrophic factors were also increased, while the concentrations of IL-7, IL-17F, CXCL1, CXCL10, EGF, and lactoferrin were reduced, in DED patients compared with healthy controls [ 25 , 26 ].…”
Section: Pathogenetic Mechanisms Of Ss and Associated Dedmentioning
confidence: 99%
“…As surrogate markers of disease severity, there are elevated concentrations of IL-1β, IL-2, IL-4, IL-6, IL-9, IL-12, IL-17A, IFN-γ, and TNF-α cytokines, and CCL2, CCL3, CCL4, and CXCL8 chemokines. The levels of MMP-9, FGF, VEGF-A, IL1RA, sICAM-1, and sTNFR1 soluble receptors, NGF, substance P, and serotonin neurotrophic factors were also increased, while the concentrations of IL-7, IL-17F, CXCL1, CXCL10, EGF, and lactoferrin were reduced, in DED patients compared with healthy controls [ 25 , 26 ].…”
Section: Pathogenetic Mechanisms Of Ss and Associated Dedmentioning
confidence: 99%
“…29 The elimination of harmful free radicals and inhibition of the formation of several toxic compounds by Lactoferrin makes it a potential biomarker for the diagnosis of relevant diseases, such as Alzheimer's Disease (AD), 30,31 Inflammatory Bowel Disease (IBD), 32 as well as tear biomarker for dry eye. 33–35…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, studies have similarly demonstrated different tear inflammatory profiles among patients with symptoms and signs of dry eye. 4 This likely explains why symptomatically, some individuals prefer cyclosporinebased products whereas others prefer lifitegrast. 5 As a community, we need to better subtype dry eye into categories based on treatable mechanisms.…”
mentioning
confidence: 99%
“…Furthermore, as we have learned from the field of uveitis, there are many different pathologic patterns of ocular inflammation, each requiring a different optimal therapy. Not surprisingly, studies have similarly demonstrated different tear inflammatory profiles among patients with symptoms and signs of dry eye . This likely explains why symptomatically, some individuals prefer cyclosporine-based products whereas others prefer lifitegrast .…”
mentioning
confidence: 99%